Characterization of the cytoplasmic filament protein gene (cfpA) of Treponema pallidum subsp. pallidum. - You, Y (1996)
Treponema pallidum and other members of the genera Treponema, Spirochaeta, and Leptonema contain multiple cytoplasmic filaments that run the length of the organism just underneath the cytoplasmic membrane. These cytoplasmic filaments have a ribbon-like profile and consist of a major cytoplasmic filament protein subunit (CfpA, formerly called TpN83) with a relative molecular weight of approximately 80,000. Degenerate DNA primers based on N-terminal and CNBr cleavage fragment amino acid sequences of T. pallidum subsp. pallidum (Nichols) CfpA were utilized to amplify a fragment of the encoding gene (cfpA). A 6.8-kb EcoRI fragment containing all but the 5' end of cfpA was identified by hybridization with the resulting PCR product and cloned into Lambda ZAP II. The 5' region was obtained by inverse PCR, and the complete gene sequence was determined. The cfpA sequence contained a 2,034-nucleotide coding region, a putative promoter with consensus sequences (5'-TTTACA-3' for -35 and 5'-TACAAT-3' for -10) similar to the sigma70 recognition sequence of Escherichia coli and other organisms, and a putative ribosome-binding site (5'-AGGAG-3'). The deduced amino acid sequence of CfpA indicated a protein of 678 residues with a calculated molecular mass of 78.5 kDa and an estimated pI of 6.15. No significant homology to known proteins or structural motifs was found among known prokaryotic or eukaryotic sequences. Expression of a LacZ-CfpA fusion protein in E. coli was detrimental to survival and growth of the host strain and resulted in the formation of short, irregular filaments suggestive of partial self-assembly of CfpA. The cytoplasmic filaments of T. pallidum and other spirochetes appear to represent a unique form of prokaryotic intracytoplasmic inclusions.